Apitherapy – the medical use of bee products - Szabat, Przemysław; Poleszak, Julita; Szabat, Marta; Boreński, Grzegorz; Wójcik, Magdalena; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Introduction: Bee products have been used by man for centuries. However, their therapeutic options are not fully understood.Aim of the study: To review research on the possibilities of using the medicinal properties of bee products.Material and method: Standard criteria were used to review literature data. Search for articles in the PubMed database was carried out using the following keywords: apitherapy, honey, bee venom, propolis, royal jelly, bee pollen.Description: Apitherapy is a healing method known to mankind since the oldest times. Due to the diverse composition, substances produced by bees show a number of activities, which include Antioxidant, immunomodulatory, antibacterial and anticancer effect. Thanks to numerous mechanisms, they have a beneficial effect on wound healing, cardiovascular diseases and metabolic disorders.Summary: Numerous properties and a wide range of activity of each bee product brings the possibility of using them in the therapy of many diseases.